The Effects of Parents' Attention and Learning Discipline on the English Learning Achievement in Junior High Schools - Sukhadman Sukhadman; Pujiati Suyata (Lingua Pedagogia, 2020)
This research aimed to desribe the effects of parents’ attention and learning discipline on the English learning achievement and  the correlation between parents’ attention and learning discipline and the English learning achievement at grade 9th in Junior High School. This research was an expost facto research. The population was 2.716 students. A sample of 337 students was established using  the proportional stratified random sampling technique. The techniques of data collection were the questionnaries and the document of students’ English learning achievement in the even of year 8 in 2012/2013. The instrument valididty was assessed in terms of the content validity using Factor Analysis. The reliabilty of the instrument was assessed using Cronbach Alpha. The data were analyzed using the Multiple Regression and partial correlation analysis. Multiple Regression test results show that parents’ attention and learning discipline simultaneously affect the English learning achivement with the value of F = 43.311 and p ≤ 0.05. Adjusted R² value = 0.197 means that the variant of the English learning achivement variable could be predicted by parents’ attention and learning discipline 19.7%. Meanwhile, according to the partial correlation analysis, parents’ attention correlates with English learning achievement (r = 0.385 and p ≤ 0.05).  Learning discipline correlates with the English learning achievement (r = 0.182 and p ≤ 0.05). Keywords: parents’ attention, learning discipline, and English learning achievement.